INOVASI MANAJEMEN PENDIDIKAN MELALUI PROGRAM PAKADES SEBAGAI MODEL PEMBERDAYAAN PENDIDIKAN DI KABUPATEN TANGERANG - Usep Saepul Mustakim (STKIP Pesisir Selatan, 2026)
The Village-Level Equivalency Education Program (PAKADES) is an educational management innovation developed by the Tangerang Regency Government to address the challenges of equity and quality improvement in rural education. The program serves as a solution to limited access to formal education by providing non-formal education services that are equivalent in terms of curriculum, learning processes, and recognition of learning outcomes through a community-based approach. This study aims to analyze the forms of educational management innovation within PAKADES and to evaluate its effectiveness as a model of community empowerment. The research employs a qualitative approach through literature review, analysis of regional education policies, and examination of program documents. The findings indicate that PAKADES has a significant positive impact, particularly in increasing educational participation among productive-age communities previously constrained by economic, geographic, and social factors. The program also expands access to education while fostering awareness of the importance of education for improving quality of life. Through the synergy of local government, non-formal education institutions, and village authorities, PAKADES has created an adaptive learning model based on local potential. The program strengthens the role of villages as centers of educational innovation and reflects the government’s commitment to achieving equitable, inclusive, and sustainable education.